Reconocimiento a los revisores del 2018 - de la Revista Cubana de Estomatología, Comité Editorial (Revista Cubana de Estomatología, 2019)
Every day, the basic standards agreed upon by the scientific editors of biomedical journals are higher. Proper evaluation of a manuscript implies knowledge, time and work. It is difficult to find people with the scientific training, experience and altruism necessary to perform the function of reviewer or referee of a scientific journal, sometimes those of higher scientific preparation reject this noble task by having excessive work, being evaluated articles for other journals , have teaching and administrative responsibilities, among others. The reviewers must know the mission and scope of the journal, the standards and the rigor required of the authors; be familiar with the topic to be evaluated; and know the state of the art of this. The main responsibility of the referee is to determine the scientific quality of the article in all its parts. Although it is sometimes criticized that the reviewer makes suggestions, these serve to contribute to the training of the authors, who sometimes know their science, but do not have enough training to translate it into an article. It is essential that the reviewers comply with the terms of the time available for the evaluation of an article, when this does not happen there are delays that result in a malfunction of the process. The authors deserve our respect and consideration and the reviewers must act ethically, when they make suggestions they must use appropriate language without hurting the author’s sensitivity. The function of the arbitrators is little recognized and misinterpreted by the authors, who do not realize that we all work to improve their article and that their results are published with the required standards; When the article is published, all the merit is received by the author. In the publication of the Cuban Journal of Stomatology, many people participate and we want to thank them. In the person of José Enrique Alfonso Manzanet, Head of the Department of Biomedical Journals, to the Medical Sciences Editorial Center because without them it would be impossible to publish the journal. Ana Dolores del Campo Peña, from the Medical Sciences Publishing Center, for her continuous work. To the section editors Jorge Luis Bécquer Águila, Isabel Martínez Brito, Rosa María González Ramos, Janet Ofelia Guevara Canales, Denia Morales Navarro and Agustín Rodríguez Soto. And mainly to our referees or reviewers for their outstanding performance.